Caracterização quali-quantitativa da bacia hidrográfica do Rio dos Bugres – MT visando o planejamento e gestão dos recursos hídricos - Fava, Rosa Augusta Crestani (2012)
This work aimed at qualitative and quantitative characterization of the Bugres river watershed through the phyisiographic study, the identification of the runoff characteristics and the diagnostic of water quality. The main spring headwater of this watershed, was modified due to the inconsistency of topographic maps, digital maps and popular knowledge. The results show a large periurban watershed, which involves six counties and one Indian land, which has an area of 2226.04 km2 , 5th order, has little tendency to flooding and drainage density (0.57 km/km2 ) that is considered poor. Meanderings occured along the main river, which has length of 136.75 km and slope equivalent to 0.001 m/m. The average mean concentration time of the basin is 31.54 hours. The maximum flow rate was 46.75 m 3 /s and the minimum flow of11.06 m 3 /s. The average speed of the Bugres river obtained was 0.46 m/s, with drastic reduction of this value in March and April (0.14 m/s and 0.12 m/s) respectively, due to the damming of the Bugres river by the Paraguay river. This phenomenon has led to critical levels of dissolved oxygen and interfered in the parameters of pH, turbidity and total solids, however, featuring a natural condition of the river. The low values found for BOD, nitrate and E. coli did not indicate contamination by domestic sewage. The 66.67% of total phosphorus values found in Bugres river which were over the limits permitted by 357/2005 Resolution for river of class 2 may be justified by the transport of soil particles and phosphorus, the basis of fertilizers used in pasture and in the cultivation of sugar cane. Water quality was verified by means of water quality index (WQI) classifying the Bugres river as regular and good quality, based on four collected points which were evaluated from October 2010 to September 2011. The basin has a large territory in constant expansion of agriculture and population, what brings the need of constant study to broaden the knowledge of the area for protection, supervision and management of water resources.